Parenting for Lifelong Health for Young Children: a randomized controlled trial of a parenting program in South Africa to prevent harsh parenting and child conduct problems. (19th September 2019) - Ward, Catherine L.; Wessels, Inge M.; Lachman, Jamie M.; Hutchings, Judy; Cluver, Lucie D.; Kassanjee, Reshma; Nhapi, Raymond; Little, Francesca; Gardner, Frances
Abstract : Background: Parenting programs suitable for delivery at scale in low‐resource contexts are urgently needed. We conducted a randomized trial of Parenting for Lifelong Health (PLH) for Young Children, a low‐cost 12‐session program designed to increase positive parenting and reduce harsh parenting and conduct problems in children aged 2–9. Methods: Two hundred and ninety‐six caregivers, whose children showed clinical levels of conduct problems (Eyberg Child Behavior Inventory Problem Score, >15), were randomly assigned using a 1:1 ratio to intervention or control groups. At t 0, and at 4–5 months ( t 1 ) and 17 months ( t 2 ) after randomization, research assistants blind to group assignment assessed (through caregiver self‐report and structured observation) 11 primary outcomes: positive parenting, harsh parenting, and child behavior; four secondary outcomes: parenting stress, caregiver depression, poor monitoring/supervision, and social support. Trial registration: ClinicalTrials.gov (NCT02165371); Pan African Clinical Trial Registry (PACTR201402000755243); Violence Prevention Trials Register (http://www.preventviolence.info/Trials?ID=24 ). Results: Caregivers attended on average 8.4 sessions. After adjustment for 30 comparisons, strongest results were as follows: at t 1, frequency of self‐reported positive parenting strategies (10% higher in the intervention group, p  =   .003), observed positive parenting (39% higher in the intervention group, p  =   .003), and observed positive child behavior (11% higher in the intervention group, p  =   .003); at t 2, both observed positive parenting and observed positive child behavior were higher in the intervention group (24%, p  =   .003; and 17%, p  =   .003, respectively). Results with p ‐values < .05 prior to adjustment were as follows: At t 1, the intervention group self‐reported 11% fewer child problem behaviors, 20% fewer problems with implementing positive parenting strategies, and less physical and psychological discipline (28% and 14% less, respectively). There were indications that caregivers reported 20% less depression but 7% more parenting stress at t 1 . Group differences were nonsignificant for observed negative child behavior, and caregiver‐reported child behavior, poor monitoring or supervision, and caregiver social support. Conclusions: PLH for Young Children shows promise for increasing positive parenting and reducing harsh parenting. Abstract : Read the Commentary on this article at doi: 10.1111/jcpp.13172